The Problems of Cancellation of Aircraft Tickets During the Covid-19 Pandemic from The Point of View of Consumer Protection in Indonesia and in the European Union - Sri Wahyuni; Esther Masri; Sufiarina (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
The emergence of the Covid-19 pandemic had a wide impact on various economic sectors, one of the largest sectors being the aviation and tourism sectors. The government has taken a policy of limiting air transportation activities that have an impact on canceled flights. The case that arises is that the canceled tickets are replaced with vouchers, this raises the question of what form of consumer protection is for airline passengers whose tickets are canceled. The method of this research is normative using the approach of laws and regulations from the point of view of the rules in Indonesia and the European Union. From the research conducted by the author, it was found that the consumer protection of airplane passengers has been reduced due to the Covid-19 pandemic.